The Aztecs, Maya, and their predecessors - Weaver, Muriel Porter, author.
1 online resource (596 pages).
Keywords: The Third Edition of this highly successful introduction to the archaeology of Mesoamerica includes full coverage of the Aztec and Maya areas in one volume. Beginning with the settling of the New World and continuing through the Spanish conquest of Mesoamerica in 1521, this completely updated textbook includes the deciphering of Maya hieroglyphs, the dynamic history of the Maya, the new royal tomb excavated at Copan, Honduras, important new discoveries at Rio Azul and Naj Tunich in Guatemala, and Caracol in Belize, ritual sacrifices on a massive scale revealed at Teotihuacan in central Mexico, and new material from Tula (Toltec capitol) and from the heart of Mexico City.